PROPOSING A REAL TIME INTERNAL INTRUSION DETECTION SYSTEM TOWARDS A SECURED DEVELOPMENT OF E-GOVERNMENT WEB SITE - Al-Khanjari, Z.; Alanee, A.; Kraiem, N.; Jamoussi, Y. (European Scientific Journal, ESJ, 2014)
As society becomes more and more reliant on software systems for its smooth functioning, software security is emerging as an important concern to many researchers in the field of Computer Science. We describe a prototype implementation based on the internal sensors to perform internal intrusion detection in e-Government website. The internal sensors consist of code source added to the e-Government website inside ISP where monitoring will take place. It shows check for specific conditions that indicate an attack is taking place, or an intrusion has occurred in a real time to building internal intrusion detection systems. These systems are based on internal sensors and classification of data collection mechanisms for intrusion detection systems. It shows that it is possible to build e-Government website which is able to detect different types of intrusions and places of implementation that are most effective in detecting different types of attacks. In this paper, we introduce the work that will attempt to show that it is possible to perform real time internal intrusion detection using small sensors embedded in e-Government website source. These sensors will look for signs of specific intrusions and will perform target monitoring by observing the behavior of the website directly in real time. In this work we speak about the image file and how to protect it.